Epidemiological survey on mange mite of rabbits in the Southern Region of Egypt - Elshahawy, Ismail; El-Goniemy, Ashraf; Ali, Esraa (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of the present study was to estimate the epidemic situation of mites, in rabbit dermatologic disease in and around Qena province, in the southern region of Egypt. Two hundred cases of dermatologic disease from the formentioned province were investigated by conducting deep skin scraping between May 2011 and October 2012. The overall prevalence was 25%. Sarcoptic scabiei uniculi (22.5%) was the most frequent mite, followed by Notoedres cati cuniculi (2.5%). To the best of our knowledge this is the first report of Notoedres cati cuniculi among studied rabbits in the study region. Study on different breeds, English represents highest prevalence of mites 30%. Moreover, there was no significant difference in the prevalence of mange mite infection between male and female rabbits (p > 0.05). Similarly, the prevalence was not significant among the age groups and rabbit breeds (p > 0.05). In conclusion, the present prevalence of mange mites was still high enough to cause significant economic losses in the study area. Therefore, strengthening the control effort was suggested.